An ethic of hospitality : the pilgrim motif in Hebrews and the refugee problem in Kenya - Choge, Emily Jeptepkeny (Eugene, Oregon : Pickwick Publications, 2020)
"In our increasingly xenophobic world, countries are turning away refugees and immigrants. Based on the situation in Kenya, this book offers a countercultural ethic of hospitality and welcome to the stranger, an ethic fraught with dangers and yet filled with great opportunities for transforming our world. Drawing on the scriptural pilgrim motif and specifically on the book of Hebrews, this study paints a picture of refugees not only as needy strangers to be herded into camps, but as brothers and sisters who bring with them treasures and talents that can enrich our understanding of our Christian identity and mission as pilgrims in the world. The hospitality practice seen in Hebrews offers hope and promise not only for refugees themselves but also for the pilgrim church. Like the ancient heroes of faith portrayed in Hebrews, we too live as pilgrims and aliens who await with hope the city whose architect and founder is God. Refugees in fact teach us how to live our pilgrim identity: they become teachers not only for the church in Kenya but also for the body of Christ worldwide." --provided by publisher, back cover
1. A hospitality ethic of pilgrims for Kenyan refugees -- 2. The refugee situation in the Horn of Africa -- 3. Responses to the refugee problem -- 4. Kenya : a refugee-hosting country -- 5. The pilgrim motif in the Book of Hebrews -- 6. The role of the Church in Kenya and the refugee problem -- 7. Recommendations and conclusions.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible -- Hermeneutics; Bible; Bible; Hospitality in the Bible; Hospitality -- Religious aspects -- Christianity; Hermeneutics; Hospitality in the Bible; Hospitality -- Religious aspects -- Christianity; Refugees; Kenya -- Refugees; Kenya; Criticism, interpretation, etc